ChemInform Abstract: Successive Regioselective Metalations of Fused Heterocycles: Synthesis of Polyfunctionalized Furo[3, 2‐b]pyridines. Issue 41 (19th September 2013) - Jasselin‐Hinschberger, Adeline; Comoy, Corinne; Chartoire, Anthony; Fort, Yves
Abstract A series of title compounds is synthesized using different lithiation methods.